Foam and rheological behavior of polydentate phosphonate-modified polymers under cement system. (5th July 2021) - Ma, Jianfeng; Shang, Yazhuo; Peng, Changjun; Liu, Honglai; Zheng, Shuzhen; Yan, Han; Ran, Qianping
Highlights: Phosphonate-modified polymers with different hydrophobic structures were synthesized. PO units affect foam properties of polymers in aqueous solution and cement mortar. Bubbles with smaller size improve the rheological properties of cement mortar. Abstract: Polymer superplasticizer and residual polyether have a key effect on the quantity and size distribution of air-voids in hardened concrete. In this study, the surface activity and foam properties of polydentate phosphonate-modified polymers RM-1 and RM-2 in aqueous solution were studied. Results revealed that the propylene oxide (PO) units in the polymer structure affected the foaming properties of polymers. The compounding performance of polymers RM-1 and RM-2 with ester-type polycarboxylate superplasticizer (PCE-1) in aqueous solution and cement mortar was also studied. This kind of phosphonate-modified polymers can be used as excellent concrete rheological modifier agents because they generate many small bubbles when compounded with PCE-1. Analysis of the foam properties of polymer RM-1 in aqueous solution and cement pore solution revealed that the calcium ions in cement pore solution are beneficial to stabilize the bubbles produced by the polymer. This study provides a new way to study the properties of phosphonate admixture and its combination with PCE from the perspective of bubble and rheology in aqueous solution and cement mortar.